Analysis of Fused Rooted Maxillary First and Second Molars with Merged and C-shaped Canal Configurations: Prevalence, Characteristics, and Correlations in a Saudi Arabian Population - Mashyakhy, Mohammed; Chourasia, Hemant Ramesh; Jabali, Ahmad; Almutairi, Abdulmajeed; Gambarini, Gianluca (Journal of endodontics, 2019)
The aims of this in vivo cone-beam computed tomographic (CBCT) study were to evaluate the prevalence, characteristics, and correlations between the fused rooted maxillary first and second molars as well as their consequent merged and C-shaped canals in a Saudi Arabian population. CBCT imaging of 726 maxillary first and second molars from 208 subjects of Saudi origin were evaluated in the present study. The prevalence of fused rooted maxillary molars, merged canals, C-shaped configurations, and correlations between the presence of fused rooted teeth between first and second molars were examined as the primary outcome. Differences by sex, location in the jaw, and bilateral symmetry (similarity between right- and left-side teeth in the same patient) were evaluated as the secondary outcome. The Z test was used for differences in the independent proportions, the chi-square test was used for differences between sex and locations, and the Cohen kappa test was used for bilateral symmetry. The kappa test was also used for intrarater reliability. A value of P < .05 was considered significant. The prevalence of fused rooted maxillary first and second molars was 7% and 21%, respectively. Within fused rooted teeth, the presence of merged canals was 8.3% and 32.1%, whereas the prevalence of C-shaped canals was 8.3% and 5.1% in first and second maxillary molars, respectively. Among 57 subjects who had fused rooted maxillary molars, 19.3% showed a correlation between first and second molars. In fused rooted maxillary molars, 3.8% first molars and 13% second molars were bilaterally symmetrical. There were no statistically significant differences between sexes and right- and left-sided fused rooted maxillary molars, merged canals, or C-shaped canals. Maxillary second molars presented more complex external and internal morphology compared with maxillary first molars, with an overall prevalence of 14% of fused rooted maxillary molars and 3.7% merged and 0.8% C-shaped canal configurations for all maxillary molars. The clinician should be aware of such challenges, and for a better treatment outcome, the use of CBCT imaging (small field of view) and an operative dental microscope can be considered when a preoperative periapical radiograph shows signs of fused rooted maxillary molars.